Polyurea coating as well as preparation method and application thereof

By using polyurea coatings with specific components, the tensile properties and tear strength of polyurea coatings are enhanced, solving the performance deficiencies of existing polyurea coatings in high-end fields. This results in a low-cost, high-performance coating suitable for corrosion protection, rust prevention, and scratch resistance.

CN120818288APending Publication Date: 2025-10-21INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202410434808.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing polyurea coatings are insufficient to meet the application requirements of high-end fields such as off-road vehicles, high-grade buildings and marine environments in terms of abrasion resistance, impact resistance and weather resistance. Moreover, they are complex to apply, not environmentally friendly and costly.

Method used

The mechanical properties of the polyurea coating are enhanced by chemical bonding. Component A consists of polyisocyanate-terminated polyethers and/or polyisocyanate-terminated polyesters and polyisocyanate-modified micro/nano silica. Component B consists of polyether polyamines and/or polyester polyamines, polyether polyols and/or polyester polyols, polyhydroxy-modified micro/nano silica and/or polyamine-modified micro/nano silica.

Benefits of technology

It significantly improves the tensile properties and tear strength of polyurea coatings, while being less expensive and offering better value for money than polyurea coatings reinforced with graphene and carbon nanotubes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004786866660000161
    Figure BDA0004786866660000161
Patent Text Reader

Abstract

The invention provides a polyurea coating as well as a preparation method and application thereof. The functional micro-nano silicon dioxide is adopted to enhance the polyurea coating, and strong chemical bonds exist between the functional micro-nano silicon dioxide and polyurea elastomer macromolecules, so that the mechanical property of the obtained polyurea coating can be remarkably enhanced. Compared with an unreinforced polyurea coating, the tensile property of the reinforced polyurea coating is improved by 30-50%, and the tear strength is improved by 30-50%. More importantly, compared with the existing graphene and carbon nanotube reinforced polyurea coating, the polyurea coating disclosed by the invention has the advantages of lower cost and higher cost performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyurea coating and a preparation method and application thereof, belonging to the technical field of polyurea. Background Art

[0002] Common anti-corrosion coatings include epoxy resins, polyurethanes, and vinyl esters, which can meet the needs of most applications. However, in applications such as off-road vehicles, high-end buildings, and marine environments, these coatings often lack the required wear resistance, impact resistance, and weather resistance. Furthermore, these coatings are complex to apply and are environmentally unfriendly, making them unsuitable for high-end applications such as corrosion prevention and protection.

[0003] Compared to polyurethane, spray polyurea elastomers cure faster and are less affected by ambient temperature and humidity during application. Compared to epoxy resins, they offer significant advantages in mechanical properties, film thickness, flexibility, and environmental friendliness. They are currently widely used in waterproofing, corrosion prevention, and military protection. In protective applications, spray polyurea cures faster than conventional materials, facilitates application, allows for continuous vertical spraying without sagging, and can be transported quickly after application without adhesion. This makes them particularly suitable for high-volume production where the number of workstations is limited.

[0004] Depending on the raw materials used to synthesize spray polyurea elastomers, they can be divided into aromatic polyurea elastomers, aliphatic polyurea elastomers, and polyaspartic polyurea elastomers. Polyurea elastomers are produced by the reaction of an isocyanate-terminated prepolymer (prepolymer) with a hard segment isocyanate and a soft segment amino-terminated polyether, and a curing agent. The curing agent includes an amino-terminated polyether and a liquid chain extender.

[0005] To further enhance the performance of polyurea coatings, filler components are often added. For example, by introducing graphene and carbon nanotubes into polyurea coatings, the tensile and impact resistance properties of the resulting polyurea coating can be significantly enhanced. While these methods are effective, they significantly increase the cost of polyurea coatings. Summary of the Invention

[0006] In order to improve the shortcomings of existing polyurea coatings, the present invention provides a polyurea coating and a preparation method and use thereof. The polyurea coating is a polyurea coating with enhanced mechanical properties. The tensile properties and impact properties (such as elongation at break and tear strength) of the polyurea coating obtained after the polyurea coating is applied are simultaneously improved, and the cost is relatively low.

[0007] The object of the present invention is achieved through the following technical solutions:

[0008] A polyurea coating comprises a component A and a component B; the component A comprises a polyisocyanate-terminated polyether and / or a polyisocyanate-terminated polyester, and polyisocyanate-modified micro-nano silica; the component B comprises a polyether polyamine and / or a polyester polyamine, a polyether polyol and / or a polyester polyol, polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica, and a chain extender.

[0009] Beneficial effects of the present invention:

[0010] The present invention provides a polyurea coating, its preparation method, and its use. The present invention utilizes functional micro-nano silica to reinforce the polyurea coating. The functional micro-nano silica and the polyurea elastomer polymer form a strong chemical bond, significantly enhancing the mechanical properties of the resulting polyurea coating. Compared to unreinforced polyurea coatings, the reinforced polyurea coating of the present invention exhibits 30-50% greater tensile properties and 30-50% greater tear strength. More importantly, compared to existing graphene- and carbon nanotube-reinforced polyurea coatings, the present polyurea coating offers lower cost and a higher cost-performance ratio. DETAILED DESCRIPTION

[0011] <Polyurea coating>

[0012] As described above, the present invention provides a polyurea coating, which includes component A and component B; component A includes polyisocyanate-terminated polyether and / or polyisocyanate-terminated polyester, and polyisocyanate-modified micro-nano silica; component B includes polyether polyamine and / or polyester polyamine, polyether polyol and / or polyester polyol, polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica, and a chain extender.

[0013] According to an embodiment of the present invention, the A component includes the following components in parts by mass:

[0014] Polyisocyanate-terminated polyether and / or polyisocyanate-terminated polyester: 100 parts by mass;

[0015] Polyisocyanate-modified micro-nano silica: 1-30 parts by mass.

[0016] According to an embodiment of the present invention, the A component includes 1 mass parts, 2 mass parts, 3 mass parts, 5 mass parts, 6 mass parts, 8 mass parts, 10 mass parts, 12 mass parts, 15 mass parts, 18 mass parts, 20 mass parts, 25 mass parts, and 30 mass parts of polyisocyanate-modified micro-nano silica.

[0017] According to an embodiment of the present invention, the B component includes the following components in parts by mass:

[0018] Polyether polyamine and / or polyester polyamine: 30-60 parts by mass;

[0019] Polyether polyol and / or polyester polyol: 30-60 parts by mass;

[0020] Polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica: 1-20 parts by mass;

[0021] Chain extender: 20-100 parts by mass.

[0022] According to an embodiment of the present invention, the B component includes 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass or 60 parts by mass of polyether polyamine and / or polyester polyamine.

[0023] According to an embodiment of the present invention, the B component includes 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass or 60 parts by mass of polyether polyol and / or polyester polyol.

[0024] According to an embodiment of the present invention, the B component includes 1 mass parts, 2 mass parts, 3 mass parts, 5 mass parts, 6 mass parts, 8 mass parts, 10 mass parts, 12 mass parts, 15 mass parts, 18 mass parts or 20 mass parts of polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica.

[0025] According to an embodiment of the present invention, the B component includes 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass, 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass, 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, 95 parts by mass or 100 parts by mass of chain extender.

[0026] According to an embodiment of the present invention, the volume ratio of the component A to the component B is 1:0.8-1.2, for example, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0027] According to an embodiment of the present invention, the component A and / or the component B further comprises auxiliary agents, including but not limited to auxiliary components commonly used in polyurea coatings such as pigments, dyes, inorganic fillers, dispersants and defoamers.

[0028] According to an embodiment of the present invention, there is no particular limitation on the specific selection of pigments, dyes, inorganic fillers, dispersants and defoamers, which can be components known in the art; preferably, they are auxiliary agents that do not react with the A component and the B component.

[0029] According to an embodiment of the present invention, the mass of the auxiliary agent accounts for 0.5-5wt% of the total mass of the A component, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%; and / or, the mass of the auxiliary agent accounts for 0.5-5wt% of the total mass of the B component, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%.

[0030] <Polyisocyanate-terminated polyether and / or polyisocyanate-terminated polyester>

[0031] According to an embodiment of the present invention, the polyisocyanate-terminated polyether includes at least one of polyisocyanate-terminated polypropylene glycol (PPG) and polyisocyanate-terminated polytetramethylene glycol (PTMEG). The polyisocyanate-terminated polyester includes at least one of polyisocyanate-terminated polycaprolactone (PCL) and polyisocyanate-terminated polycarbonate (PCDL).

[0032] According to an embodiment of the present invention, the number average molecular weight of the polyisocyanate-terminated polyether or polyisocyanate-terminated polyester is 500-5000 g / mol, preferably 800-4000 g / mol, for example 1000-3000 g / mol, such as 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol or 3000 g / mol.

[0033] According to an embodiment of the present invention, the content of isocyanate in the polyisocyanate-terminated polyether is 5-25wt%, for example, 5wt%, 10wt%, 15wt%, 20wt% or 25wt%. The content of isocyanate in the polyisocyanate-terminated polyester is 5-25wt%, for example, 5wt%, 10wt%, 15wt%, 20wt% or 25wt%.

[0034] According to an embodiment of the present invention, the polyisocyanate-terminated polyether is prepared by the following method: a polyether polyamine and a polyisocyanate that have been subjected to heat dehydration are mixed and reacted to prepare the polyisocyanate-terminated polyether.

[0035] According to an embodiment of the present invention, the polyisocyanate-terminated polyester is prepared by the following method: polyester polyamine and polyisocyanate after heating and dehydration are mixed and reacted to prepare the polyisocyanate-terminated polyester.

[0036] According to an embodiment of the present invention, 20-40 parts by mass (such as 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass or 40 parts by mass) of the heat-dehydrated polyether polyamine and 40-60 parts by mass (such as 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass or 60 parts by mass) of the polyisocyanate are mixed and reacted to prepare the polyisocyanate-terminated polyether.

[0037] According to an embodiment of the present invention, 20-40 parts by mass (such as 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass or 40 parts by mass) of the heat-dehydrated polyester polyamine and 40-60 parts by mass (such as 40 parts by mass, 45 parts by mass, 50 parts by mass, 55 parts by mass or 60 parts by mass) of the polyisocyanate are mixed and reacted to prepare the polyisocyanate-terminated polyester.

[0038] According to an embodiment of the present invention, the reaction temperature is 75-95° C., for example, 75° C., 80° C., 85° C., 90° C. or 95° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0039] According to an embodiment of the present invention, the temperature of the heating dehydration is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C. The heating dehydration time is 0.5-4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours or 4 hours. The heating dehydration is carried out under vacuum conditions.

[0040] According to an embodiment of the present invention, polyether polyamine or polyester polyamine is added to a reactor, stirred and heated to 80-120° C., vacuumed and kept warm for 0.5-4 hours for dehydration to obtain the heated and dehydrated polyether polyamine or heated and dehydrated polyester polyamine.

[0041] According to an embodiment of the present invention, the purpose of the heating dehydration is to remove impure water.

[0042] According to an embodiment of the present invention, the polyisocyanate includes diisocyanate and polymethylene polyphenyl polyisocyanate.

[0043] According to an embodiment of the present invention, the polyisocyanate includes 60-95 parts by mass (such as 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass or 95 parts by mass) of diisocyanate and 5-40 parts by mass (such as 5 parts by mass, 10 parts by mass, 15 parts by mass, 20 parts by mass, 25 parts by mass, 30 parts by mass, 35 parts by mass or 40 parts by mass) of polymethylene polyphenyl polyisocyanate.

[0044] According to an embodiment of the present invention, the diisocyanate includes at least one of isophorone diisocyanate IPDI, xylylene isocyanate (XDI), cyclohexylene dimethylene diisocyanate (HXDI), 4,4-dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI) and diphenylmethane diisocyanate (MDI).

[0045] According to an embodiment of the present invention, the polymethylene polyphenyl polyisocyanate includes at least one of diphenylmethane diisocyanate, triphenylmethane triisocyanate or polymethylene polyphenyl polyisocyanate having a functionality greater than three.

[0046] According to an embodiment of the present invention, the polyether polyamine includes at least one of polyamino-terminated polypropylene glycol (PPG) and polyamino-terminated polytetramethylene glycol (PTMEG), and the polyester polyamine includes at least one of polyamino-terminated polycaprolactone (PCL) and polyamino-terminated polycarbonate (PCDL).

[0047] According to an embodiment of the present invention, the polyether polyamine or polyester polyamine is, for example, selected from the polyether polyamines or polyester polyamines disclosed in U.S. Patent Nos. 5,962,618 and 6,013,755, or selected from at least one of Jeffamine D-2000 (available from Huntsman Petrochemicals Corp.), Jeffamine T-5000 (available from Huntsman Petrochemicals Corp.), Ethacure 100 (available from Albemarle Corp., Baton Rouge, LA), Unilink 4200 (available from UOP, Des Plaines, IL), and Unilink 4100 (available from UOP, Des Plaines, IL).

[0048] According to an embodiment of the present invention, the number average molecular weight of the polyether polyamine or polyester polyamine is 500-5000 g / mol, preferably 800-4000 g / mol, for example 1000-3000 g / mol, such as 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol or 3000 g / mol.

[0049] <Polyisocyanate-modified micro-nano silica>

[0050] According to an embodiment of the present invention, the polyisocyanate-modified micro-nano silica is micro-nano silica containing isocyanate groups on the surface.

[0051] According to an embodiment of the present invention, the number of isocyanate groups on the surface of the polyisocyanate-modified micro-nano silica satisfies: 5-100 isocyanate groups / nm 2 , preferably 15-80 isocyanate groups / nm 2 , more preferably 30-80 isocyanate groups / nm 2 , such as 40 isocyanate groups / nm 2 , 50 isocyanate groups / nm 2 , 60 isocyanate groups / nm 2 , 70 isocyanate groups / nm 2 The term "isocyanate group / nm 2 " refers to the number of isocyanate groups on the surface of the polyisocyanate-modified micro-nano silica per square nanometer.

[0052] According to an embodiment of the present invention, the mass of the isocyanate groups in the polyisocyanate-modified micro-nano silica accounts for 30-60% of the total mass of the polyisocyanate-modified micro-nano silica, for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0053] According to an embodiment of the present invention, the average particle size of the polyisocyanate-modified micro-nano silica is 10 nm-200 μm, preferably 20 nm-150 μm, more preferably 50 nm-100 μm, for example, 50 nm, 100 nm, 200 nm, 300 nm, 350 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 120 μm, 125 μm, 150 μm, 160 μm, 180 μm or 200 μm.

[0054] According to an embodiment of the present invention, the polyisocyanate-modified micro-nano silica is prepared by the following method:

[0055] The polyhydroxy-modified micro-nano silica and diisocyanate are mixed and reacted to prepare the polyisocyanate-modified micro-nano silica.

[0056] According to an embodiment of the present invention, 100 parts by mass of polyhydroxy-modified micro-nano silica and 50-100 parts by mass (such as 50 parts by mass, 55 parts by mass, 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, 95 parts by mass or 100 parts by mass) of diisocyanate are mixed and reacted to prepare the polyisocyanate-modified micro-nano silica.

[0057] According to an embodiment of the present invention, the reaction temperature is 50-80° C., for example, 50° C., 55° C., 60° C., 65° C., 70° C., 75° C. or 80° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0058] According to an embodiment of the present invention, the reaction is carried out in the presence of an organic solvent. The organic solvent includes at least one of an ester solvent, an alcohol solvent, and an ether solvent. For example, the ester solvent includes at least one of methyl acetate, ethyl acetate, and butyl acetate; the alcohol solvent includes at least one of isopropyl alcohol, n-butanol, isobutanol, and sec-butanol; and the ether solvent includes at least one of tetrahydrofuran, ethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.

[0059] According to an embodiment of the present invention, the diisocyanate is defined as above.

[0060] According to an embodiment of the present invention, the polyhydroxy-modified micro-nano silica is micro-nano silica containing hydroxyl groups on the surface; preferably, the polyhydroxy-modified micro-nano silica is micro-nano silica containing silanol groups Si-OH on the surface.

[0061] According to an embodiment of the present invention, the number of hydroxyl groups contained on the surface of the polyhydroxy-modified micro-nano silica satisfies: 5-100 hydroxyl groups / nm 2 , preferably 15-80 hydroxyl groups / nm 2 , more preferably 30-80 hydroxyl groups / nm 2 , such as 40 hydroxyl groups / nm 2 、50 hydroxyl groups / nm 2 、60 hydroxyl groups / nm 2 , 70 hydroxyl groups / nm 2 The term "hydroxyl group / nm 2 " means the number of hydroxyl groups on the surface of the multi-hydroxy modified micro-nano silica per square nanometer.

[0062] According to an embodiment of the present invention, the mass of hydroxyl groups in the polyhydroxy-modified micro-nano silica accounts for 30-60% of the total mass of the polyhydroxy-modified micro-nano silica, for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0063] According to an embodiment of the present invention, the average particle size of the polyhydroxy-modified micro-nano silica is 10nm-200μm, preferably 20nm-150μm, more preferably 50nm-100μm, for example, 50nm, 100nm, 200nm, 300nm, 350nm, 400nm, 500nm, 550nm, 600nm, 700nm, 800nm, 900nm, 1μm, 2μm, 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 120μm, 125μm, 150μm, 160μm, 180μm or 200μm.

[0064] According to an embodiment of the present invention, the polyhydroxy-modified micro-nano silica can be prepared by the method described in the literature (Ceramics International 35 (2009) 1015-1019, Journal of Colloid and Interface Science 352 (2010) 278-284), or can be purchased from commercial products.

[0065] <Polyether polyamine and / or polyester polyamine>

[0066] According to an embodiment of the present invention, the polyether polyamine is defined as above.

[0067] According to an embodiment of the present invention, the polyester polyamine is defined as above.

[0068] According to an embodiment of the present invention, the polyether polyamine is preferably a polyether polyamine that has been dehydrated by heating. The polyester polyamine is preferably a polyester polyamine that has been dehydrated by heating.

[0069] According to an embodiment of the present invention, the temperature of the heating dehydration is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C. The heating dehydration time is 0.5-4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours or 4 hours. The heating dehydration is carried out under vacuum conditions.

[0070] According to an embodiment of the present invention, polyether polyamine or polyester polyamine is added to a reactor, stirred and heated to 80-120° C., vacuumed and kept warm for 0.5-4 hours for dehydration to obtain the heated and dehydrated polyether polyamine or heated and dehydrated polyester polyamine.

[0071] According to an embodiment of the present invention, the purpose of the heating dehydration is to remove impure water.

[0072] <Polyether polyol or polyester polyol>

[0073] According to an embodiment of the present invention, the polyether polyol includes at least one of polyoxypropylene glycol, polytetramethylene glycol and tetramethylene glycol-propylene oxide copolymer. The polyester polyol includes at least one of polycaprolactone glycol PCL, polycarbonate glycol PCDL, polypropylene glycol PPG and polytetramethylene glycol PTMEG.

[0074] According to an embodiment of the present invention, the number average molecular weight of the polyether polyol or polyester polyol is 500-5000 g / mol, preferably 800-4000 g / mol, for example 1000-3000 g / mol, such as 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol or 3000 g / mol.

[0075] According to an embodiment of the present invention, the polyether polyol is preferably a polyether polyol that has been dehydrated by heating. The polyester polyol is preferably a polyester polyol that has been dehydrated by heating.

[0076] According to an embodiment of the present invention, the temperature of the heating dehydration is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C. The heating dehydration time is 0.5-4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours or 4 hours. The heating dehydration is carried out under vacuum conditions.

[0077] According to an embodiment of the present invention, polyether polyol or polyester polyol is added to a reactor, stirred and heated to 80-120° C., vacuumed and kept warm for 0.5-4 hours for dehydration to obtain the heated dehydrated polyether polyol or heated dehydrated polyester polyol.

[0078] According to an embodiment of the present invention, the purpose of the heating dehydration is to remove impure water.

[0079] <Polyamino-modified micro-nano silica and / or polyhydroxy-modified micro-nano silica>

[0080] According to an embodiment of the present invention, the polyamino-modified micro-nano silica is micro-nano silica containing amino groups on the surface; preferably, the polyamino-modified micro-nano silica is micro-nano silica containing silicon amino groups Si-NH2 on the surface.

[0081] According to an embodiment of the present invention, the number of amino groups on the surface of the multi-amino-modified micro-nano silica satisfies: 5-100 amino groups / nm 2 , preferably 15-80 amino groups / nm 2 , more preferably 30-80 amino groups / nm 2 , such as 40 amino groups / nm 2 , 50 amino groups / nm 2 , 60 amino groups / nm 2 , 70 amino groups / nm 2 The term "amino / nm 2 " means the number of amino groups on the surface of the multi-amino-modified micro-nano silica per square nanometer.

[0082] According to an embodiment of the present invention, the mass of the amino groups in the polyamino-modified micro-nano silica accounts for 30-60% of the total mass of the polyamino-modified micro-nano silica, for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0083] According to an embodiment of the present invention, the average particle size of the polyamino-modified micro-nano silica is 10nm-200μm, preferably 20nm-150μm, more preferably 50nm-100μm, for example, 50nm, 100nm, 200nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 2μm, 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 120μm, 125μm, 150μm, 160μm, 180μm or 200μm.

[0084] According to an embodiment of the present invention, the polyamino-modified micro-nano silica is prepared by the following method:

[0085] The polyhydroxy modified micro-nano silica and aminoalkyl alkoxy silicon are mixed and reacted to prepare the polyamino modified micro-nano silica.

[0086] According to an embodiment of the present invention, 100 parts by mass of polyhydroxy-modified micro-nano silica and 50-100 parts by mass (such as 50 parts by mass, 55 parts by mass, 60 parts by mass, 65 parts by mass, 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, 90 parts by mass, 95 parts by mass or 100 parts by mass) of aminoalkyl alkoxy silicon are mixed and reacted to prepare the polyamino-modified micro-nano silica.

[0087] According to an embodiment of the present invention, the reaction temperature is 50-80° C., for example, 50° C., 55° C., 60° C., 65° C., 70° C., 75° C. or 80° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0088] According to an embodiment of the present invention, the reaction is carried out in the presence of an organic solvent. The organic solvent includes at least one of an ester solvent, an alcohol solvent, and an ether solvent. For example, the ester solvent includes at least one of methyl acetate, ethyl acetate, and butyl acetate; the alcohol solvent includes at least one of isopropyl alcohol, n-butanol, isobutanol, and sec-butanol; and the ether solvent includes at least one of tetrahydrofuran, ethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.

[0089] According to an embodiment of the present invention, the polyhydroxy-modified micro-nano silica is defined as described above.

[0090] According to an embodiment of the present invention, the aminoalkylalkoxysilane is a silane containing an amino group, an alkyl group and an alkoxy group, including at least one of 3-aminopropyl-trimethoxysilane, 3-aminopropyl-triethoxysilane, phenylaminomethyltriethoxysilane, phenylaminomethyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltriethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldiethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane and aminoethylaminoethylaminopropyltriethoxysilane.

[0091] <Chain Extender>

[0092] According to an embodiment of the present invention, the chain extender includes one or more combinations of diethyltoluenediamine, dimethylthiotoluenediamine, N,N'-dialkylmethyldiphenylamine, 4,4-bis-sec-butylaminodiphenylmethane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, diethyltoluenediamine, diacetyl-m-phenylenediamine and isophoronediamine.

[0093] <Preparation Method of Polyurea Coating>

[0094] The present invention also provides a method for preparing the polyurea coating, the method comprising the following steps:

[0095] Component A and optionally added auxiliary agents are mixed to obtain a first component; component B and optionally added auxiliary agents are mixed to obtain a second component; when in use, the first component and the second component are mixed to prepare the polyurea coating.

[0096] According to an embodiment of the present invention, the mixing is performed by stirring or spraying, for example, by using a spraying machine to mix and then spraying on the surface of the object to be protected; or by stirring and pre-mixing and then applying to the surface of the object to be protected.

[0097] According to an embodiment of the present invention, the mixing temperature is 20-180°C, preferably 30-150°C, more preferably 60-120°C, for example 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.

[0098] According to an embodiment of the present invention, the component A is prepared by the following method:

[0099] The component A is prepared by mixing and reacting a polyisocyanate-terminated polyether and / or a polyisocyanate-terminated polyester with polyisocyanate-modified micro-nano silica.

[0100] According to an embodiment of the present invention, the reaction temperature is 75-95° C., for example, 75° C., 80° C., 85° C., 90° C. or 95° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0101] According to an embodiment of the present invention, the component A is prepared by the following method:

[0102] The component A is prepared by mixing polyether polyamine and / or polyester polyamine, polyisocyanate, and polyisocyanate-modified micro-nano silica, reacting, and vacuum dehydrating.

[0103] According to an embodiment of the present invention, the reaction temperature is 75-95° C., for example, 75° C., 80° C., 85° C., 90° C. or 95° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0104] According to an embodiment of the present invention, the temperature of the vacuum dehydration is 80-120° C., for example, 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., or 120° C. The time of the vacuum dehydration is 0.5-4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours, or 4 hours.

[0105] According to an embodiment of the present invention, the B component is prepared by the following method:

[0106] The polyether polyamine and / or polyester polyamine, polyether polyol and / or polyester polyol, polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica, and a chain extender are mixed, reacted, and vacuum-dehydrated to prepare the B component.

[0107] According to an embodiment of the present invention, the reaction temperature is 50-80° C., for example, 50° C., 55° C., 60° C., 65° C., 70° C., 75° C. or 80° C. The reaction time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0108] According to an embodiment of the present invention, the temperature of the vacuum dehydration is 80-120° C., for example, 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., or 120° C. The time of the vacuum dehydration is 0.5-4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours, or 4 hours.

[0109] <Applications of Polyurea Coatings>

[0110] As mentioned above, the present invention also provides the use of the polyurea coating for corrosion protection, rust prevention and scratch resistance.

[0111] As mentioned above, the present invention also provides uses of the polyurea coating, which is used in the fields of automobiles, chemical equipment, bridges, and fixed buildings.

[0112] <Polyurea coating>

[0113] The present invention also provides a polyurea coating, which is prepared by the polyurea coating.

[0114] According to an embodiment of the present invention, the polyurea coating is prepared by the following method: coating or spraying the above-mentioned polyurea coating onto the surface of a substrate and curing it at room temperature to obtain the polyurea coating.

[0115] According to an embodiment of the present invention, the polyurea coating comprises polyurea elastomer and silica.

[0116] According to an embodiment of the present invention, the mass of the silica accounts for 1-20 wt% of the total mass of the polyurea coating, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt% or 20 wt%.

[0117] According to an embodiment of the present invention, the mass of the polyurea elastomer accounts for 80-99wt% of the total mass of the polyurea coating, for example, 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%.

[0118] According to an embodiment of the present invention, the elongation at break of the polyurea coating is greater than 410%, for example, 420%-550%.

[0119] According to an embodiment of the present invention, the tear strength of the polyurea coating is greater than 140 N / mm, for example, 140 N / mm-160 N / mm.

[0120] According to an embodiment of the present invention, the tensile strength of the polyurea coating is greater than 29 MPa, for example, 29.5 MPa-40 MPa.

[0121] The technical solutions of the present invention will be described in further detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are encompassed within the scope of protection that the present invention is intended to protect.

[0122] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the reagents, materials, etc. used in the following examples are all commercially available unless otherwise specified.

[0123] The performance tests of the polyurea coatings in the following examples were obtained by testing according to the method specified in GB / T 23446-2009.

[0124] Example 1

[0125] According to the literature Ceramics International 35 (2009) 1015-1019, a polyhydroxy modified nano-silica with an average particle size of 350 nm was prepared, and its hydroxyl content was 33 / nm 2 .

[0126] Preparation of component A:

[0127] 1-A1: 100 kg of polyhydroxy-modified nano-silica, 60 kg of diphenylmethane diisocyanate, and 300 L of ethyl acetate were mixed, heated to 60° C., reacted for 3 hours, and centrifuged to obtain polyisocyanate-modified nano-silica.

[0128] 1-A2: Dehydrate 500 kg of polyether polyamine Jeffamine D-2000 at 120° C. and a vacuum degree of 0.09 MPa for 2 hours, and then cool to obtain heat-dehydrated polyether polyamine Jeffamine D-2000.

[0129] 1-A3: Heat 200 kg of polyisocyanate (e.g., Wanhua Chemical Wannate MDI-50) to 50°C, add 30 kg of the polyisocyanate-modified nanosilica prepared in 1-A1, and slowly add dropwise 150 kg of the heat-dehydrated polyether polyamine Jeffamine D-2000 prepared in 1-A2 within 1 hour. Raise the temperature to 80°C, react for 3 hours, and vacuum dehydrate to obtain a prepolymer component A with an -NCO content of 18 wt%.

[0130] Preparation of component B:

[0131] 1-B1: 100 kg of polyhydroxy-modified nano-silica, 60 kg of 3-aminopropyltrimethoxysilane and 300 L of tetrahydrofuran were mixed, heated to 60° C., reacted for 3 hours, and centrifuged to obtain polyamino-modified nano-silica.

[0132] 1-B2: 150 kg of polytetrahydrofuran diol (molecular weight 1500 g / mol), 120 kg of Jeffamine T-5000, 80 kg of dimethylthiotoluene diamine, 30 kg of the polyamino-modified nanosilica prepared in 1-B1, 0.3 kg of dispersant Tego Dispers 610, and 1.5 kg of defoamer Tego Foamex N were added to a reaction kettle, the temperature was raised to 60° C., the reaction was carried out for 3 hours, vacuum dehydration was carried out, and stirring was carried out for 30 minutes to obtain component B.

[0133] Using a Graco H-40 two-component sprayer, component A and component B were heated to 80°C and sprayed in a volume ratio of 1:1 on a polypropylene plate to form a 1.5mm thick coating. After curing at room temperature for 48 hours, the polyurea coating was peeled off, and specimens were cut as required and tested for performance.

[0134] Comparative Example 1

[0135] Other operations are the same as in Example 1, except that nano-silicon dioxide is not added to components A and B.

[0136] Comparative Example 2

[0137] Other operations are the same as in Example 1, except that the nano-silicon dioxide added to components A and B is commercially available, with an average particle size of 350 nm and a hydroxyl content of less than 3 / nm. 2 .

[0138] Examples 2-5

[0139] Other operations were the same as in Example 1, except that the amount of polyhydroxy-modified nano-silica used in component A and component B was different, as shown in Table 1. The polyhydroxy-modified nano-silica was prepared according to the literature (Ceramics International 35 (2009) 1015–1019).

[0140] Table 1 Composition and performance test results of polyurea coatings of Examples and Comparative Examples

[0141]

[0142] As can be seen from Table 1, the functional micro-nano silica can significantly enhance the mechanical properties of the obtained polyurea coating.

[0143] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

Claims

1. A polyurea coating, comprising component A and component B; component A comprising a polyisocyanate-terminated polyether and / or a polyisocyanate-terminated polyester, and polyisocyanate-modified micro-nano silica; and component B comprising a polyether polyamine and / or polyester polyamine, a polyether polyol and / or polyester polyol, polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica, and a chain extender.

2. The polyurea coating according to claim 1, wherein The A component includes the following components in parts by mass: Polyisocyanate-terminated polyether and / or polyisocyanate-terminated polyester: 100 parts by mass; Polyisocyanate-modified micro-nano silica: 1-30 parts by mass; And / or, the B component includes the following components in parts by weight: Polyether polyamine and / or polyester polyamine: 30-60 parts by mass; Polyether polyol and / or polyester polyol: 30-60 parts by mass; Polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica: 1-20 parts by mass; Chain extender: 20-100 parts by mass. Preferably, the volume ratio of the component A to the component B is 1:0.8-1.

2.

3. The polyurea coating according to claim 1 or 2, wherein: The polyisocyanate-terminated polyether includes at least one of polyisocyanate-terminated polypropylene glycol PPG and polyisocyanate-terminated polytetramethylene glycol PTMEG; the polyisocyanate-terminated polyester includes at least one of polyisocyanate-terminated polycaprolactone PCL and polyisocyanate-terminated polycarbonate PCDL; And / or, the content of isocyanate in the polyisocyanate-terminated polyether is 5-25 wt %, and the content of isocyanate in the polyisocyanate-terminated polyester is 5-25 wt %. Preferably, the polyisocyanate-terminated polyether is prepared by the following method: a polyether polyamine and a polyisocyanate that have been subjected to heat dehydration are mixed and reacted to prepare the polyisocyanate-terminated polyether. Preferably, the polyisocyanate-terminated polyester is prepared by the following method: mixing and reacting the polyester polyamine and polyisocyanate after heating and dehydration to prepare the polyisocyanate-terminated polyester. Preferably, 20-40 parts by mass of the heat-dehydrated polyether polyamine and 40-60 parts by mass of the polyisocyanate are mixed and reacted to prepare the polyisocyanate-terminated polyether. Preferably, 20-40 parts by mass of the heat-dehydrated polyester polyamine and 40-60 parts by mass of polyisocyanate are mixed and reacted to prepare the polyisocyanate-terminated polyester. Preferably, the reaction temperature is 75-95° C., and the reaction time is 1-5 hours. Preferably, the temperature of the heating dehydration is 80-120° C., and the time of the heating dehydration is 0.5-4 hours. Preferably, the polyisocyanate includes diisocyanate and polymethylene polyphenyl polyisocyanate. Preferably, the polyisocyanate comprises 60-95 parts by mass of diisocyanate and 5-40 parts by mass of polymethylene polyphenyl polyisocyanate. Preferably, the polyether polyamine includes at least one of polyamino-terminated polypropylene glycol (PPG) and polyamino-terminated polytetramethylene glycol (PTMEG), and the polyester polyamine includes at least one of polyamino-terminated polycaprolactone (PCL) and polyamino-terminated polycarbonate (PCDL).

4. The polyurea coating according to any one of claims 1 to 3, wherein: The polyisocyanate-modified micro-nano silica is micro-nano silica containing isocyanate groups on the surface. Preferably, the number of isocyanate groups on the surface of the polyisocyanate-modified micro-nano silica satisfies the following conditions: 5-100 isocyanate groups / nm 2 . Preferably, the mass of the isocyanate groups in the polyisocyanate-modified micro-nano silica accounts for 30-60% of the total mass of the polyisocyanate-modified micro-nano silica. Preferably, the average particle size of the polyisocyanate-modified micro-nano silica is 10 nm-200 μm. Preferably, the polyisocyanate-modified micro-nano silica is prepared by the following method: The polyhydroxy-modified micro-nano silica and diisocyanate are mixed and reacted to prepare the polyisocyanate-modified micro-nano silica. Preferably, 100 parts by mass of polyhydroxy-modified micro-nano silica and 50-100 parts by mass of diisocyanate are mixed and reacted to prepare the polyisocyanate-modified micro-nano silica. Preferably, the reaction temperature is 50-80° C., and the reaction time is 1-5 hours.

5. The polyurea coating according to any one of claims 1 to 4, wherein: The polyhydroxy-modified micro-nano silica is micro-nano silica containing hydroxyl groups on the surface; preferably, the polyhydroxy-modified micro-nano silica is micro-nano silica containing silicon hydroxyl groups Si-OH on the surface. Preferably, the number of hydroxyl groups on the surface of the polyhydroxy-modified micro-nano silica satisfies the following conditions: 5-100 hydroxyl groups / nm 2 . Preferably, the mass of the hydroxyl groups in the polyhydroxyl-modified micro-nano silica accounts for 30-60% of the total mass of the polyhydroxyl-modified micro-nano silica. Preferably, the average particle size of the polyhydroxy-modified micro-nano silica is 10 nm-200 μm. Preferably, the polyamino-modified micro-nano silica is micro-nano silica containing amino groups on the surface; preferably, the polyamino-modified micro-nano silica is micro-nano silica containing silicon amino groups Si-NH2 on the surface. Preferably, the number of amino groups on the surface of the polyamino-modified micro-nano silica satisfies the following conditions: 5-100 amino groups / nm 2 . Preferably, the mass of the amino groups in the polyamino-modified micro-nano silica accounts for 30-60% of the total mass of the polyamino-modified micro-nano silica. Preferably, the average particle size of the polyamino-modified micro-nano silica is 10 nm-200 μm. Preferably, the polyamino-modified micro-nano silica is prepared by the following method: The polyhydroxy modified micro-nano silica and aminoalkyl alkoxy silicon are mixed and reacted to prepare the polyamino modified micro-nano silica. Preferably, 100 parts by mass of polyhydroxy-modified micro-nano silica and 50-100 parts by mass of aminoalkyl alkoxy silicon are mixed and reacted to prepare the polyamino-modified micro-nano silica. Preferably, the reaction temperature is 50-80° C., and the reaction time is 1-5 hours. Preferably, the aminoalkylalkoxysilane is a silane containing an amino group, an alkyl group and an alkoxy group, including at least one of 3-aminopropyl-trimethoxysilane, 3-aminopropyl-triethoxysilane, phenylaminomethyltriethoxysilane, phenylaminomethyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltriethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldiethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane and aminoethylaminoethylaminopropyltriethoxysilane.

6. The polyurea coating according to any one of claims 1 to 5, wherein: The polyether polyol includes at least one of polyoxypropylene glycol, polytetramethylene glycol and tetramethylene glycol-propylene oxide copolymer; the polyester polyol includes at least one of polycaprolactone glycol PCL, polycarbonate glycol PCDL, polypropylene glycol PPG and polytetramethylene glycol PTMEG. Preferably, the chain extender includes one or more combinations of diethyltoluenediamine, dimethylthiotoluenediamine, N,N'-dialkylmethyldiphenylamine, 4,4-bis-sec-butylaminodiphenylmethane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, diethyltoluenediamine, diacetyl-m-phenylenediamine and isophoronediamine.

7. A method for preparing a polyurea coating according to any one of claims 1 to 6, comprising the steps of: Component A and optionally added auxiliary agents are mixed to obtain a first component; component B and optionally added auxiliary agents are mixed to obtain a second component; when in use, the first component and the second component are mixed to prepare the polyurea coating. Preferably, the mixing temperature is 20-180°C. Preferably, the A component is prepared by the following method: The component A is prepared by mixing and reacting a polyisocyanate-terminated polyether and / or a polyisocyanate-terminated polyester with polyisocyanate-modified micro-nano silica. Preferably, the A component is prepared by the following method: The component A is prepared by mixing polyether polyamine and / or polyester polyamine, polyisocyanate, and polyisocyanate-modified micro-nano silica, reacting, and vacuum dehydrating. Preferably, the B component is prepared by the following method: The polyether polyamine and / or polyester polyamine, polyether polyol and / or polyester polyol, polyhydroxy-modified micro-nano silica and / or polyamino-modified micro-nano silica, and a chain extender are mixed, reacted, and vacuum-dehydrated to prepare the B component.

8. Use of the polyurea coating according to any one of claims 1 to 6 for corrosion protection, rust prevention and scratch resistance; or for use in the fields of automobiles, chemical equipment, bridges and fixed buildings.

9. A polyurea coating, wherein the polyurea coating is prepared by the polyurea coating according to any one of claims 1 to 6.

10. The polyurea coating according to claim 9, wherein The polyurea coating comprises a polyurea elastomer and silicon dioxide, wherein the mass of the silicon dioxide accounts for 1-20 wt% of the total mass of the polyurea coating; and / or the mass of the polyurea elastomer accounts for 80-99 wt% of the total mass of the polyurea coating. Preferably, the elongation at break of the polyurea coating is 410% or more; and / or the tear strength of the polyurea coating is 140 N / mm or more; and / or the tensile strength of the polyurea coating is 29 MPa or more.

Citation Information

Patent Citations

  • Polyurea spray railcar lining systems

    US5962618A

  • Method of preparing an aliphatic polyurea spray elastomer system

    US6013755A

Cited By

  • Bridge waterproof anti-slip coating and production process thereof

    CN121406226A